Optimization of PCR conditions for Agriophyllum, Haloxylon and Salsola microsatellite markers (International Journal of Biology and Chemistry, 2020)
Microsatellites or Simple Sequence Repeat (SSR) are among the most informative and popular types of molecular markers for assessment of genetic diversity, population structure, construction of genetic maps, phylogenetics, phylogeography, systematics, etc. Hence, for reliable inference of results, optimization of various conditions involved in polymerase chain reaction (PCR) is a pre-requisite. The usage of the essential PCR components in optimal concentrations, as well as PCR conditions, determines the success of amplification. The present study was carried out to optimize conditions of PCR for further assessment of the genetic diversity of eight species in genera Agriophyllum, Haloxylon, and Salsola that belong to the Chenopodiaceae Vent. family. The list of species includes Agriophyllum squarrosum, Agriophyllum minus, Haloxylon aphyllum, Haloxylon persicum, Haloxylon ammodendron, Salsola arbuscula, Salsola arbusculiformis, and Salsola chiwensis. These selected species are widespread in desert regions of Kazakhstan and have great importance for sand dunes fixing, animal feeding, and other purposes.